2018
DOI: 10.1111/jfpp.13789
|View full text |Cite
|
Sign up to set email alerts
|

Improving quality and shelf-life of minced beef using irradiated olive leaf extract

Abstract: The present study aims at evaluating antioxidant and antimicrobial activities of olive (Olea europaea) leaves extracts (OLE) obtained from olive leaves (OL) irradiated at the dose levels 5, 10, and 15 kGy. The antioxidant activity of the extracts was estimated using the radical scavenging activity, and ferric reducing antioxidant power. The antimicrobial activity of the extracts was assessed against Bacillus cereus, Staphylococcus aureus, Escherichia coli, Klebsiella pneumonia, Pseudomonas aeruginosa, and Salm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 43 publications
10
2
0
Order By: Relevance
“…These results are in agreement with Cardoso et al [41]. Our results showed that OLE had positive impact in decreasing the psychrophilic count in the treated samples as compared to the control ones; this result was supported by Shalaby et al [30]. Table 6.…”
Section: Total Psychrotrophic Count (Tpc)supporting
confidence: 93%
See 4 more Smart Citations
“…These results are in agreement with Cardoso et al [41]. Our results showed that OLE had positive impact in decreasing the psychrophilic count in the treated samples as compared to the control ones; this result was supported by Shalaby et al [30]. Table 6.…”
Section: Total Psychrotrophic Count (Tpc)supporting
confidence: 93%
“…Our findings revealed that lower pH values in treated poultry meat were obtained with OLE as compared to the control samples, and this may be linked to the active compounds present in olives' leaf extract. Our observations are supported by the findings of Shalaby et al [30], who reported lower pH values in minced meat treated with OLE as a consequence of the nature and the properties of the active phenolic compounds present in OLE. These results thus indicate that the application of OLE as an antimicrobial agent influences the pH of poultry meat during the refrigeration storage.…”
Section: Hydrogen Ion Concentration (Ph)supporting
confidence: 93%
See 3 more Smart Citations